2005
DOI: 10.1124/jpet.104.082131
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C βII Peptide Inhibitor Exerts Cardioprotective Effects in Rat Cardiac Ischemia/Reperfusion Injury

Abstract: Ischemia followed by reperfusion (I/R) in the presence of polymorphonuclear leukocytes (PMNs) results in a marked cardiac contractile dysfunction. A cell-permeable protein kinase C (PKC) ␤II peptide inhibitor was used to test the hypothesis that PKC ␤II inhibition could attenuate PMN-induced cardiac dysfunction by suppression of superoxide production from PMNs and increase NO release from vascular endothelium. The effects of the PKC ␤II peptide inhibitor were examined in isolated ischemic (20 min) and reperfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 41 publications
0
34
0
1
Order By: Relevance
“…The SO release from Poly Morphonuclear Leukocytes (PMNs) was measured spectrophotometrically (model 260 Gilford, Nova Biotech; El Cajon, CA) by the reduction of ferricytochrome c as previously described [23]. The PMNs (5 × 10 6 ) were resuspended in 450 μl PBS and incubated with ferricytochrome c (100 µM, Sigma Chemical) in a total volume of 900 μl PBS in the presence or absence of varying concentrations of apocynin (MW = 166 g/mol; Sigma …”
Section: Measurement Of So Release From Rat Pmnsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SO release from Poly Morphonuclear Leukocytes (PMNs) was measured spectrophotometrically (model 260 Gilford, Nova Biotech; El Cajon, CA) by the reduction of ferricytochrome c as previously described [23]. The PMNs (5 × 10 6 ) were resuspended in 450 μl PBS and incubated with ferricytochrome c (100 µM, Sigma Chemical) in a total volume of 900 μl PBS in the presence or absence of varying concentrations of apocynin (MW = 166 g/mol; Sigma …”
Section: Measurement Of So Release From Rat Pmnsmentioning
confidence: 99%
“…Regarding NADPH oxidase and eNOS uncoupling, activation of Protein kinase C beta II isoform is mostly responsible for NADPH oxidase activation and inhibition of eNOS activity [23,33]. Our previous studies found that a selective PKC beta II peptide inhibitor significantly attenuated oxidative stress in hind limb I/R and restored post-reperfused cardiac function in isolated I/R hearts [23,33,34].…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Doing so facilitates study of the process in the intact animal. Several publications have shown that the isolated rat aortic segment model is a prognostic indicator of whole organ function (15,(24)(25)(26)(27). Overall, the experimental setup is cost effective in that small amount of reagents, tissues, or cells are needed to generate reliable data.…”
Section: Discussionmentioning
confidence: 99%
“…At the conclusion of the experiment, the aortic segments are blotted and weighed, and results are usually reported as moles of NO released per gram of tissue (15,(23)(24)(25)(26)(27). Figure 3A is an illustration depicting the experimental setup for rat aortic segment tissue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation